Vets' and Pet Owners' Views About Antibiotics for Companion Animals and the Use of Phages as an Alternative - Rhys-Davies, Lucy; Ogden, Jane (Frontiers in Veterinary Science, 2020)
Antimicrobial resistance (AMR) is a global health burden. Although a complex and multi-faceted problem, inappropriate antibiotic use has repeatedly been identified as one of the main drivers of the acceleration and spread of AMR. Behaviours associated with antibiotic prescription and use have been extensively investigated in human medicine, and in the livestock sector of veterinary medicine. There is now a growing interest in the factors that drive inappropriate antibiotic use in companion animal medicine, as the significance of antimicrobial use in this sector is being recognised. Additionally, the possibility of an alternative antimicrobial, phage therapy, being implemented into companion animal medicine is explored in this study. Interviews revealed complexities in the vet-owner relationship including conflicting perceptions of responsibility regarding antibiotic prescription and use, distrust of vets’ intentions and misconception of clients’ needs. A need for alternative antimicrobials was evident, as all vets were able to report difficulties finding antibiotics to treat infections as a common occurrence. Questionnaire results indicated that vets and pet owners are open to the use of phage therapy in companion animals. This study shows that an alternative antimicrobial such as phage therapy could be accepted into companion animal medicine in the UK, however, effective communication between vets and pet owners is vital if antibiotic use is to be reduced and new antimicrobials successfully implemented.